Plymouth Tube Company : how to build ownership consensus - Ward, John L., 1945- (SAGE Knowledge. Cases., 2016)
Plymouth Tube, a family business, was a manufacturer of precision tubing and extruded shapes for aerospace, desalination, medical, mining, energy, and water industries globally. Founded in 1924, as of 2012 it employed 770 people at thirteen plants in seven U.S. states and had sales of about $240 million. The family had twenty members across three generations, including spouses. The board was composed of eight members, three from the family and five who were independent. Stacy, age 30, was the only fifth-generation family member working for the company. Her father, Van, age 64 and a fourth-generation member, had been in the business for forty years and had succeeded his father as president, CEO, and chairman.In early 2013, management presented a very large expansion project that was riskier than previous recent investments to the board, and requested the board's approval. Independent board members asked Van to obtain feedback from the family about the proposal. Van asked Stacy to direct the process for informing the family, asking for their input, and communicating it back to the board.How should Stacy conduct the process? What should be done with the information once it has been gathered? Should family members be involved in this type of business decision? Based on the information given in the case, is this a good investment?